Juridical Implications of the Covid-19 Pandemic on Credit Agreements in Indonesia - Elvandi Christian Saragih (Faculty of Law, Merdeka University Surabaya, 2021)
The Covid-19 pandemic has resulted in many people losing their jobs, if the person concerned is a bank debtor, it can result in him failing to make credit instalments to the bank as the creditor. This study aims to find out how the legal consequences of the Covid-19 Pandemic have on credit agreements in Indonesia and how to resolve them in case of default. The results showed that the Covid-19 Pandemic resulted in difficulties for debtors to pay credit instalments to banks as creditors and made debtors in default. Settlement steps that can be taken if the debtor is in default are Termination of the Agreement or Postponement of Debt Payment Obligations. If the cause of the debtor's inability to carry out his obligations as a result of a decrease in income during the Covid-19 Pandemic, the settlement using the Postponement of Debt Payment Obligation is the most appropriate option because in the future after the Covid-19 Pandemic can be resolved, the debtor is considered still can settle its obligations as stated in the Credit Agreement